EFEKTIVITAS PERENCANAAN DAN PENGEMBANGAN SISTEM INFORMASI - ., Bambang Widarno (Universitas Slamet Riyadi, 2008)
Abstract The fact show us that information technology changes the way organizations compete. It become a strategic tool to attain their competitive advantage. We found that, implementation a new system may arise problems: anxienty and social pressure. Individual may be willing to perceive and use a new technology or system because of their manager or peer pressure. Finally, conclusion suggest that top management support, hardware and software, quality of system, informations, and service, individual aspects (skills and knowledge), and purpose of systems affeceted these dimension of system information acceptance. Â Keywords: information system, mount acceptance, management support, service quality